The crunching munching caterpillar - Cain, Sheridan; Tickle, Jack (London : Little Tiger Press, 2002)
Caterpillar wants to fly like Butterfly, Bumblebee, and Sparrow, and Butterfly thinks his wish may come true.
3.7
K-3.
K-3
Keywords: Butterflies -- Fiction; Caterpillars -- Fiction; Flight -- Fiction; Butterflies -- Fiction; Caterpillars -- Fiction; Flight -- Fiction